Condomínios horizontais fechados : segregadores ou segregados? - um estudo de caso no município de Maringá-Pr - Galvão, Altair Aparecido (2007)
an space full of social differences, these condominiums show themselves as segregator areas, affecting values of accessibility, traffic freedom and equality, substituting them for a system which has inequality, differentiation and limit monitoring as main values.